2022
DOI: 10.3389/fphar.2022.963066
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a novel SNAT2 (SLC38A2) inhibitor reveals synergy with glucose transport inhibition in cancer cells

Abstract: SNAT2 (SLC38A2) is a sodium-dependent neutral amino acid transporter, which is important for the accumulation of amino acids as nutrients, the maintenance of cellular osmolarity, and the activation of mTORC1. It also provides net glutamine for glutaminolysis and consequently presents as a potential target to treat cancer. A high-throughput screening assay was developed to identify new inhibitors of SNAT2 making use of the inducible nature of SNAT2 and its electrogenic mechanism. Using an optimized FLIPR membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 69 publications
0
22
1
Order By: Relevance
“…The previous reports demonstrated that inhibition of glucose uptake has a synergistic effect with the inhibition of glutamine uptake in pancreatic cancer cells. 20 However, it may not exhibit significant abnormality when the glucose uptake pathway is activated, and glutamine uptake compensates for energy when glucose uptake is inhibited. Therefore, we additionally estimated the correlation of GLUT1 with glutamine transporters and found that ASCT2 was significantly correlated with GLUT1 (Pearson correlation, P = 5.68 × 10 −12 , r = 0.48, Figure 1G).…”
Section: T H Imentioning
confidence: 99%
“…The previous reports demonstrated that inhibition of glucose uptake has a synergistic effect with the inhibition of glutamine uptake in pancreatic cancer cells. 20 However, it may not exhibit significant abnormality when the glucose uptake pathway is activated, and glutamine uptake compensates for energy when glucose uptake is inhibited. Therefore, we additionally estimated the correlation of GLUT1 with glutamine transporters and found that ASCT2 was significantly correlated with GLUT1 (Pearson correlation, P = 5.68 × 10 −12 , r = 0.48, Figure 1G).…”
Section: T H Imentioning
confidence: 99%
“…Of course, this approach requires a large library of chemically diverse compounds as well as a scalable assay that can screen many compounds at a time. An example of this approach has recently been used to discover inhibitors of SNAT2 by screening a library of 33,934 compounds [ 32 ]. However, a more focused screen can be implemented if resources are limited or if only low-throughput assays are available.…”
Section: Discovering Amino Acid Transporter Inhibitorsmentioning
confidence: 99%
“…Here, it was shown that SNAT1 was inhibited by GPNA, GHX, and BS, whereas only GPNA and BS could significantly inhibit SNAT2 [ 22 ]. Later, it was shown that GHX inhibits SNAT2 with an IC 50 of 0.33 mM [ 32 ]. However, these compounds could also inhibit ASCT2, SNAT4, and SNAT5, highlighting their lack of specificity [ 22 ].…”
Section: Sodium-coupled Neutral Amino Acid Transporter 1 and 2 (Snat1/2)mentioning
confidence: 99%
See 1 more Smart Citation
“…Glucose metabolism is the first and most widely studied metabolic abnormality in cancer cells ( Figure 1 ) [ 21 , 22 , 23 , 24 ]. Normal cells metabolize glucose into carbon dioxide and water through oxygen-consuming mitochondrial metabolism in physiological conditions, but convert glucose into lactic acid (glycolysis) in a low oxygen and anaerobic environment [ 25 ].…”
Section: Glucose Metabolismmentioning
confidence: 99%